Renal Adverse Reaction Secondary to Check-point Inhibitors in Metastatic Renal Cancer - Lacambra, Marta Guerra; Martinez, Miguel Angel Gonzalez; Chumillas, Vanesa García; Tejero, Francisco Gutierrez (Journal of Clinical Nephrology, 2024)
Immune Checkpoint Inhibitors (PCIs,) are monoclonal antibodies directed against immune checkpoint regulatory molecules. These antibodies inhibit T-cell activation and prolong survival in patients with different types of cancer. However, they can produce adverse effects related to the immune response such as renal damage. We present the clinical case of a 75-year-old man with a personal history of Chronic Kidney Disease (CKD) and metastatic renal cancer with lung, bone, and mediastinal involvement. He started treatment with immunotherapy with Nivolumab-Ipilimumab. Then, after 4 cycles of immunotherapy, the patient was admitted to the Urology Department for an adverse reaction to immunotherapy with the development of nephritis and toxic hepatitis. Despite treatment with methylprednisolone, he evolved poorly, and a palliative approach was finally decided. The incidence of acute renal failure attributed to PCIs is estimated at 2% - 3%, being grade I-II in most cases. Among the renal complications associated with PCIs, acute interstitial nephritis is the most predominant with an incidence of 80% - 90% of cases. In addition, an increased risk is observed in patients with intermediate or poor risk metastatic renal cancer. Despite their fundamental role in metastatic renal cancer, we must take into account the potential for renal failure as an adverse effect of PCIs, especially in patients with previous CKD.